2002
DOI: 10.1021/ic011035i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Coordination to Rh(I), and Hydroformylation Catalysis of New β-Aminophosphines Bearing a Dangling Nitrogen Group:  An Unusual Inversion of a Rh-Coordinated P Center

Abstract: Variants of the beta-aminophosphine L(1) [Ph(2)PCH(2)CH(Ph)NHPh] containing additional nitrogen donor functions have been prepared. These functions are branched off the C atom adjacent to the P atom, or the P atom itself. Ligand [Ph(2)PCH(o-C(6)H(4)NMe(2))CH(Ph)NHPh] has been obtained as a mixture of two diastereomers L(3A) and L(3B) by lithiation of L(2) [Ph(2)PCH(2)(o-C(6)H(4)NMe(2))] with n-BuLi followed by PhCH=NPh addition and hydrolysis. The diastereomers have been separated by fractional crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…This investigation completes our recent studies on the Rh I coordination chemistry of P,N ligands. [15,18] Indeed, we have already reported that complex RhCl(COD)(α-P,N-2) (complex 1) adopts a κ 1 -P coordination mode both in the solid state and in solution and that an analogous monodentate coordination mode is also adopted in the dicarbonyl complex RhCl(CO) 2 (α-P,N-2) (IIα, see Scheme 2). [18] The latter was obtained by ligand exchange from RhCl(COD)(α-P,N-2) (COD = 1,5-cyclooctadiene) under high CO pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation completes our recent studies on the Rh I coordination chemistry of P,N ligands. [15,18] Indeed, we have already reported that complex RhCl(COD)(α-P,N-2) (complex 1) adopts a κ 1 -P coordination mode both in the solid state and in solution and that an analogous monodentate coordination mode is also adopted in the dicarbonyl complex RhCl(CO) 2 (α-P,N-2) (IIα, see Scheme 2). [18] The latter was obtained by ligand exchange from RhCl(COD)(α-P,N-2) (COD = 1,5-cyclooctadiene) under high CO pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Separate work has shown that β-P,N ligands in Rh I complexes can adopt a monodentate κ 1-P- [19] or a κ 2 -P,N-coordination mode. [15,20] Nevertheless, no direct evidence for a hemilabile character has been reported so far for β-P,N ligands in Rh I complexes. This behavior was only suggested for a few cationic complexes of type [Rh(COD)(β-P,N)] + in order to rationalize a rapid fluxional process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when a pyridinylphosphane is only P-coordinated in a Pd II complex, the dangling amine function acts then as a "proton messenger" in alkyne methoxycarbonylation catalysis, [2] whereas a selective P,N chelation of a chiral phosphanediamine induces an effective chiral field in the rhodium complex leading to a higher selectivity in asymmetric hydrogenation of acrylic acid. [7] In our laboratory, we have developed different access ways to chiral α- [11] or β-P,N [12,13] and mixed α,β-and β,γ-P,P,N [14] ligands and their coordination properties have been explored in copper(), [15] palladium(), [13,16] and rhodium() complexes [14,17,18] Recently, we have examined the co- and PhCD(CH 2 D)CHO (α,β-D 2 ) were also produced. This result suggests a reversible deprotonation assisted by an intramolecular H-bonding interaction between the dangling ammonium function and the carbonyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands 34 and 35, developed by Andrieu, bear a further nitrogen group which allows for two possible P-N co-ordination modes. [11] With rhodium, however, only binding through the phosphorus and the secondary amine is observed. No application of these ligands in asymmetric catalysis has yet been reported.…”
Section: Amino N Donor Phosphine P Donormentioning
confidence: 99%